Biodegradation of organic liquid waste by using consortium bacteria as material preparation of environmental pollution course textbook - Dora Dayu Rahma Turista (University of Muhammadiyah Malang, 2017)
Organic waste is one waste type which oftenly pollutes the waters. Biodegradation can be used as an environmental remedy solution that is contaminated by organic matter. This research aimed to determine the ability of bacteria consortium in degrading of organic liquid waste, and construct the textbook for Environmental Pollution subject based on research of biodegradation organic waste by using bacteria consortium. This research was done through two stages. The first stage was an experimental research by using Randomized Complete Designe with bacterial type treatment and 3 repetitions, while the second phase of research was a developmental research from the first stage. The results of the first phase showed that the combination of 3 indigenous isolats bacteria (Enterobacter gergoviae, Vibrio parahaemolyticus, and Pseudomonas stutzeri) was the highest potential bacteria in decreasing BOD (71.75% ), COD (74.40%), TSS (58.44%), and increasing DO (84.15%). The second phase was Educational Research and Development of teaching materials which refers to the development model of Borg & Gall. The stages of research were: Research and Information Collecting, Planning, Develop Preliminary Form of Product, Preliminary Field Testing and Main Product Revision which was produced as textbook for the Environmental Pollution course entitled Biodegradation Organic Waste by Using Bacteria Consortium.